The Influence of Identity Politics in Contemporary Islam - Karimullah, Suud Sarim; Bahrudin, Moh.; Istadi, Istadi (Universitas Islam Negeri Raden Intan Lampung, 2023)
The study investigates the significant impact of identity politics in contemporary Islam on political and social stability, considering the crucial role of media and communication in such dynamics. This study uses a literature study method that involves an integrative and comprehensive analysis of literature to collect, review, and analyze various sources of relevant information. The study results stated that identity politics in contemporary Islam is central to shaping political and social dynamics worldwide. By influencing the perceptions and actions of individuals and groups, identity politics in Islam can significantly impact political and social stability within a country, especially in intergroup tensions. In addition, the role of media and communication has also proved crucial in shaping the image and narrative of Islamic identity politics, both positively and negatively. Therefore, a deep understanding of the complexities of identity politics in Islam and concerted efforts to promote mutual understanding, dialogue, and peace are key to confronting the challenges of identity politics in contemporary Islam.